Description of Nothotylenchus savadkoohensis n. sp. (Rhabditida, Anguinidae) from Iran based on morphological and molecular data - Rezaei Soheila; Pourjam Ebrahim; Atighi Mohammad Reza; Pedram Majid (Journal of Nematology)
Nothotylenchus savadkoohensis n. sp. was recovered from rotten wood samples of an unidentified forest tree in the Mazandaran province and described herein. It is mainly characterized by an elongated conoid tail ending in a sharply pointed tip and four lines in the lateral field. Females of the new species have 379–662 μm long bodies with 5.8–6.9 μm long stylets ending in fine posteriorly sloping knobs, the metacorpus not valvate, the pharyngeal bulb slightly overlapping the intestine, and the vulva at 76.5–84.0% of body length. Males are also common and have 13.0–14.5 μm long spicules and bursa cloacal. By having an elongated conoid tail and four lines in the lateral field, the new species comes close to four known species, namely N. acris, N. acutus, N. antricolus, and N. truncatus. The morphological differences between the new species and the abovementioned species are discussed. The new species was sequenced for its D2–D3 segment of LSU and ITS rDNA regions. In the LSU phylogenetic tree, the currently available LSU sequences of the genus Nothotylenchus occupied distant placements from each other and the LSU sequence of the new species formed clade with a sequence assigned to Neotylenchus sp. In ITS phylogeny, the newly generated sequence of the new species formed a clade with a clade that includes sequences of Ditylenchus sp. and Neomisticius platypi and N. variabilis.